PHYSIOTHERAPY MANAGEMENT POST RECONSTRUCTION ANTERIOR CRUCIATE LIGAMENT: A CASE STUDY - Nurhidayah, Indah Suci; Rahayu, Umi Budi; Mardianto, Halim (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Anterior Cruciate Ligament (ACL) is one of the ligaments present in the knee and serves as a stabilizer of the anterior translation of the femur bone. Non-contact injuries are most common in athletes, usually due to sudden shaft changes resulting in tibia translation of the femur. About 60% of sports injuries are most common in the lower limbs, as many as 16% of injuries are caused by torn ligaments from the knee. Post-reconstruction rehabilitation of ACL aims to prevent complications such as swelling, limited scope of joint motion, muscle weakness, decreased balance and restoration of knee functional abilities Case Presentation: A 23-year-old patient came to one of the hospitals in Semarang with a diagnosis of sinistra ACL rupture, underwent reconstruction 2 months ago. Currently the patient undergoes a phase 2 physiotherapy program because he still complains of mild pain, joint stiffness when waking up, limited joint movement. Management and Outcome: Therapy is carried out for 4 weeks, with an exercise program using static bicycle, lunges, single leg, squat, single leg with cone, side step with theraband. Some tests are performed such as pain measurement using NRS (Numeric Rating Scale), measurement of joint sphere of motion using goneometer, and atrophy measurement using meterline. Discussion: Exercises given in patients post ACL reconstruction aim to improve susceptible joint motion, stimulate blood circulation, maintain muscle elasticity and reduce pain. Significant loss of function as well as inhibition of nerves can lead to atrophy. It causes quadriceps to become weak. To train the strength of the hamstring muscles and quadriceps can use close kinetic chain exercises to produce co-contraction of the muscles around the joints. Conclusion: In this case, it shows that close kinetic chain exercises can increase the range of motion of the joints, reduce pain, and prevent atrophy.